The Influence of Learning Motivation on The Improvement of Learning English Class V Students of SDN Sukaharja 1 Telukjambe Timur Karawang - Tarpan Suparman (Jurnal Sekolah Dasar, 2021)
The purpose of this study was to determine the difference in high learning outcomes between high and low learning motivation, and the difference in low learning outcomes between high and low learning motivation held in SD Negeri Sukaharja 1, Telukjambe Timur District, Karawang Regency. The method used in this research is the comparative method, which is to compare the learning motivation with the learning outcomes of the fifth grade elementary school students. With observation techniques, questionnaires, literature studies, and documentation studies. The results of testing the first hypothesis show that the average score of high learning outcomes with high motivation is 78.86 with a standard deviation of 6.87 higher than the average score of high learning outcomes with low motivation, namely 71.40 with a standard deviation of 2.51. The results of homogeneity testing of the variance of high learning outcomes between high motivation and low motivation. Fcount of 10.96 while Ftable at a significance level of 0.95 (α = 0.05) is 4.88 and a significance level of 0.99 (α = 0.01) is 10.45. This means that Fcount = 10.96> 4.88 = Ftable (0.95; 7; 5) and Fcount = 10.96> 10.45 = Fcount (0.99; 7; 5)., T-test calculation. with the results of t count of 3,971 greater than t table of 2,228 (α = 0.05) and 3,165 (α = 0.01). Then the test results prove that there are differences in high learning outcomes between high motivation and low motivation. So that one of the efforts to maintain the learning outcomes of the fifth grade students of SDN Sukaharja 1 is the high motivation given and the ability of IQ which is quite high and the willingness to learn independently. The second hypothesis testing shows that the average score of low learning outcomes with high motivation is 61.83 with a standard deviation of 2.86 higher than the average score of low learning outcomes with low motivation, which is 58.83 with a standard deviation of 2.40. The results of the homogeneity test of variance for low learning outcomes between high motivation and low motivation, Fcount of 1.42, while Ftable at a significance level of 0.95 (α = 0.05) is 4.48 and a significance level of 0.99 (α = 0.01) is 8.47. This means that Fcount = 1.42 <4.48 = Ftable (0.95; 6; 6) and Fcount = 1.42 <8.47 = Ftable (0.99; 6; 6). Then the test results prove that there is a difference in low learning outcomes between high motivation and low motivation. So that one of the efforts to improve the learning outcomes of the fifth grade students of SDN Sukaharja 1 is by providing intensive motivation and giving more homework.